(untitled) (Sir Salimullah Medical College Journal, 2022)
Background: Emergencies in ENT practice has a wide spectrum and management of each condition requires specialized skills. Crucial decisions are necessary to save patients life in hurried situations. Objectives: This study is carried out with an objective to find out pattern of ENT emergencies in tertiary level hospital. Methods: This is a cross sectional study was done in two major tertiary level hospitals (Dhaka Medical College Hospital, Sir Salimullah Medical College Mitford Hospital) of Dhaka, Bangladesh. This study was conducted in a period of six months and took into account all inpatient and outpatient emergencies in this period. These included 496 patients either admitted as emergency or took emergency treatment without admission from department of ENT and Head-Neck surgery of two tertiary level hospitals. Results: 496 patients of between age ranges 2 months-80 years with a mean age 26.3 years were included. Male female ratio was 1.9:1.55.65% patients are from rural area. The total throat related cases were maximum (40.52%) in comparison to ear (32.26%) and nose (27.22%). Inflammatory condition in pharynx (46.27%) is the most common among throat related emergencies, followed by foreign body in throat (32.26%). Fish bone impaction is the most common (33.36%) emergencies among foreign body in throat. Foreign body in throat was mostly seen in 0 to 10 age group. Acute upper respiratory tract infection is the highest (27.96%) among the pharyngeal emergencies. Laryngeal emergencies with stridor were most common (47.62%) among laryngeal, tracheal and bronchial emergencies other than foreign body. Among the otological emergencies external ear emergencies other than foreign body (40%) was most common. Vegetables foreign body in the ear was most common (40%) among the foreign body in ear. Foreign body in ear mostly found in 0 to 10 age group. Traumatic injury to external ear is the most common (18.75%) among external ear emergencies other than foreign body. Among the sinonasal emergencies epistaxis was most common (39.26%). Most of the cases were managed surgically (71.97%) 87.5% cases were recovered from emergencies with overall mortality of (1.21%). Conclusion: Epistaxis emerged as the leading cause of ENT emergencies followed by foreign body in ENT region. Most of the ENT emergencies were managed surgically under local anaesthesia. So, presence of otolaryngological department in thana and district level hospital could avoid unnecessary referral. Sir Salimullah Med Coll J 2022; 30: 67-74